IMPLIKATUR PERCAKAPAN DALAM FILM AJI MUMPUNG DI TRANS TV: KAJIAN WACANA PRAGMATIK - Widia Nurmadyah; Sisilya Saman; Patriantoro Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine the conversational implicatures in the film Aji Mumpung onTrans Tv. The research method used is descriptive in the form of qualitative research. Thedata source of this research is the Aji Mumpung film on Trans Tv and the data is aconversation or dialogue contained in the Aji Mumpung film on Trans Tv. Data collectionwas carried out using the listening method with basic techniques: tapping and advancedtechniques: free tapping and conversational techniques and note-taking techniques. Thedata collection tool used is the researcher himself as the key instrument. The technique oftesting the validity of the data used is the persistence of observers and the adequacy ofreferences. Data analysis technique that contains types of implicatures based on theimplied pragmatic function in the film Aji Mumpung on Trans Tv with receptive, directive,expressive, commissive, and declarative studies.Keywords: Conversational Implicature, Film, Speech Act, Pragmatic Function,Dialogue.